2008
DOI: 10.3141/2069-03
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Driver Behavior within a Signalized Intersection Approach Decision–Dilemma Zone

Abstract: This study uses data gathered in a field test on 60 test participants to develop models that characterize driver brake perception–reaction times (PRTs), brake times, and stop–go decisions at the onset of a yellow indication at a high-speed signalized intersection approach. The study demonstrates that driver PRTs are influenced only by the driver's time to intersection (TTI) at the onset of the yellow indication. The driver PRT is found to increase linearly with TTI and is not affected by the vehicle speed (in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 7 publications
5
23
0
Order By: Relevance
“…A multiple linear regression analysis results suggested that approach speed and distance from the intersection at yellow onset had the strongest effect on BPRT. A similar conclusion was made in a controlled road experimental research (Rakha et al, 2008). Such a research also validated that BPRT was not influenced by driver age and gender and the yellow-onset speed between 54 and 88 km/h.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…A multiple linear regression analysis results suggested that approach speed and distance from the intersection at yellow onset had the strongest effect on BPRT. A similar conclusion was made in a controlled road experimental research (Rakha et al, 2008). Such a research also validated that BPRT was not influenced by driver age and gender and the yellow-onset speed between 54 and 88 km/h.…”
Section: Introductionsupporting
confidence: 76%
“…Among the three types of driver's PRT research, naturalistic studies have the highest validity. Nevertheless, they are also limited, because it is impossible to investigate the impacts of some individual related factors (such as driver age and gender) or measure mental processing and movement times separately (ElShawarby et al, 2013;Rakha et al, 2008;Setti et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A review of these research efforts is provided in research studies such as Abbas and Ghanipoor Machiani (2013); Adam et al (2009);Jahangiri et al (2015); Papaioannou (2007); Ghanipoor Machiani and Abbas (2014a,b); Abbas et al (2014a); Rakha et al (2008) and Sharma et al (2011). The most relevant research regarding our study is on collision and safety measures in dilemma zones.…”
Section: Introductionmentioning
confidence: 90%
“…A field investigation study also showed that younger drivers with poor driving records were more likely to run yellow signal indications (Retting and Williams, 1996). Rakha et al (2008) showed that different age groups had different dilemma zone boundaries and older driver were found to have a closer dilemma zone to intersection than younger drivers. Based on the National Motor Vehicle Crash Causation Survey (NMVCCS) data, different age groups showed different attributes related to crash occurrences.…”
Section: Introductionmentioning
confidence: 95%